2007
DOI: 10.1002/art.22500
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical course of Behçet's disease in the Reggio Emilia area of Northern Italy: A seventeen‐year population‐based study

Abstract: Objective. To investigate the epidemiology and clinical course of Behçet's disease (BD) over a 17-year period in a defined area of northern Italy. Methods. All patients with incident BD diagnosed over a 17-year period (from January 1, 1988 to December 31, 2004) living in the Reggio Emilia area were identified through the following sources: physicians at Reggio Emilia Hospital, medical practitioners, and community-based specialists. We identified all patients registered in a centralized index and in the Reggio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(26 citation statements)
references
References 31 publications
2
23
0
1
Order By: Relevance
“…El Menyawi et al [9] from Egypt reported OU to be the most frequent onset manifestation (63.4 %), followed by GU (26.9 %) and deep venous thrombosis (7.9 %). In the recent study by Pipitone et al [10], OU (78.3 %), GU (29.2 %) and eye involvement (20 %), and in a previous study by Salvarani et al [11], OU (77.8 %), GU (16.7 %) and EN (22.2 %) were reported to be the most common onset presentations in an Italian population. Shafie et al [12] from Iran reported OU to be the most frequent onset manifestation (76.9 %), followed by ocular involvement (11.0 %) and GU (10.3 %).…”
Section: Discussionmentioning
confidence: 78%
“…El Menyawi et al [9] from Egypt reported OU to be the most frequent onset manifestation (63.4 %), followed by GU (26.9 %) and deep venous thrombosis (7.9 %). In the recent study by Pipitone et al [10], OU (78.3 %), GU (29.2 %) and eye involvement (20 %), and in a previous study by Salvarani et al [11], OU (77.8 %), GU (16.7 %) and EN (22.2 %) were reported to be the most common onset presentations in an Italian population. Shafie et al [12] from Iran reported OU to be the most frequent onset manifestation (76.9 %), followed by ocular involvement (11.0 %) and GU (10.3 %).…”
Section: Discussionmentioning
confidence: 78%
“…The findings are consistent with those in previous hospital-based studies, which reported that 19%Y27% of patients with BD did not present with oral ulcers at disease onset. 26 These patients having no oral ulcers were never diagnosed as having BD based on the ISG criteria, 3 in which oral ulcers are considered a prerequisite for the diagnosis of BD. Indeed, as shown in Table 7, 23 of 279 (8%) patients in the previous group satisfied the ISG criteria more than 3.3 years after satisfying the Japanese criteria for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of a higher frequency of erythema nodosum in female patients and of papulopustular lesions in male patients among our patients are in accordance with previous studies performed in Turkish patients with BD, 22,23 whereas no difference was found related to those manifestations between sexes in BD patients from other population groups. 20,24,25 The use of non-immunosuppressive agents for less severe BD as first line is based on positive results of previous studies. 26Y30 Although azathioprine has been shown to control mucocutaneous and articular manifestations of BD in a placebocontrolled randomized trial, and methotrexate was reported in small uncontrolled observational studies, the latter is preferred for the treatment of our BD patients who present only mucocutaneous and joint complaints.…”
Section: Discussionmentioning
confidence: 99%